Pyramid Resistance Training Programs: Which Style is Most Effective?. (November 2021) - Mang, Zachary; Beam, Jason; Kravitz, Len
Abstract : Summary Statement Reverse pyramid training and linear pyramid training are both effective resistance training programs for increasing total volume load during each session, which leads to chronic increases in strength. Fitness professionals are encouraged to try both with their clients and tailor resistance training programs to their preference. Apply It!: By reading this article, health and fitness professionals will learn: There is a strong relationship between total volume load (TVL), muscular strength, and skeletal muscle hypertrophy. Resistance training with pyramid repetition schemes are an effective way to increase TVL during a training session. Linear pyramid training (LPT), also known as DeLorme training, involves a systematic increase in intensity from set to set. Contrarily, reverse pyramid training (RPT), also known as Oxford training, involves a systematic decrease in intensity from set to set. The literature consistently shows that RPT and LPT are both effective at increasing muscular strength; however, people may enjoy RPT more than LPT because the session feels easier as fatigue accumulates.